2020
DOI: 10.1155/2020/5463652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xuefu Zhuyu Decoction on Cell Migration and Ocular Tumor Invasion inDrosophila

Abstract: Xuefu Zhuyu Decoction (XFZYD), a Traditional Chinese Medicine (TCM) decoction mainly for treating blood stasis syndrome, has been widely investigated and applied in clinic and in laboratory. XFZYD contains 11 herbs and has been identified to promoting blood circulation to remove blood stasis for cardiovascular disease. Meanwhile, blood stasis is directly related to malignant tumor according to TCM basic theory. However, the effects of XFZYD on tumor metastasis and the underlying mechanisms are still largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…It has the effects of promoting blood circulation, removing blood stasis, promoting qi, and relieving pain. The prescription mainly treats blood stasis syndrome in the chest [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has the effects of promoting blood circulation, removing blood stasis, promoting qi, and relieving pain. The prescription mainly treats blood stasis syndrome in the chest [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study showed that XFZYD inhibits tumour cell migration by regulating MMP1 expression ( Wang et al, 2020 ). Moreover, the JNK-activated transcription complex (AP-1) regulates the expression of MMP1 ( Uhlirova and Bohmann, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional prescriptions were prepared by the aqueous extraction method as previously described ( Wang et al, 2020 ). The XFZYD extract was stored at −80°C, freeze-dried with a lyophiliser, and reconstituted in ddH 2 O to obtain a final stock concentration of 780 g/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined drugs of one dose (75 g) were weighed and soaked in 1.5 L of double-distilled water (ddH 2 O) for 12 h ( Wang et al, 2020 ), followed by heating for 2 h. Next, the extract was separated and centrifuged at 4,200 × g for 30 min at 4°C, and the residue was collected to repeat the abovementioned steps. The two supernatants were then mixed and filtered by vacuum filtration with a 0.45-µm filter.…”
Section: Methodsmentioning
confidence: 99%